Integrated Marketing Communication Activities of PT. Prima Inti Nusa in Building a Positive Corporate Image - Simamora, Andreas Julangdi Java; Kurniawati, Dewi; Zulkarnain, Iskandar (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze and evaluate the integrated marketing communication activities carried out by PT. Prima Inti Nusa in building a positive corporate image, as well as to analyze and evaluate the supporting and inhibitingfactors in building its positive image. The theory used in this research is Marketing Communication Theory. The research method used is qualitative research with constructivism as its core paradigm. The number of informants in this study, reaching data saturation, is nine people divided into two categories: four key informants and five triangulation informants. Data collection in this study is conducted through interviews and nonparticipant observations. The results show that to build a positive image manifested through word of mouth, PT. Prima Inti Nusa uses a mix of sales promotion and personal selling. Supporting factors include the positive attitude ofthe marketing team and a mindset ofnot being easily satisfied, while inhibitingfactors include the negative attitude ofthe marketing team, a mindset of being easily satisfied, and negative issues spread by competitors